Single-nucleotide polymorphism of interleukin-10 promoter (IL-10 -819C/T) in leprosy patients with and without erythema nodosum leprosum, and household contacts - Arif, Sitti M.; Massi, Nasrum (Narra J, 2023)
Leprosy, caused by Mycobacterium leprae, is a chronic infectious disease that impacts the skin and peripheral nerves, causing long-term disability. The invasion of M. leprae into the body triggers immunologic responses and single single-nucleotide polymorphisms in cytokine-encoding genes may influence predisposition and susceptibility, possibly predicting the incidence of leprosy reactions. The aim of this study was to assess the gene polymorphism of interleukin-10 promoter IL-10 −819C/T in leprosy patients, leprosy patients with erythema nodosum leprosum (ENL) reaction, and household contacts. A total of 54 individuals were included, with 18 in each group. Skin smear and histopathologic examinations were used to confirm the diagnosis of leprosy and ENL. The polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) technique was used to determine the polymorphism. The results confirmed the presence of polymorphism of which all TT, CT, and CC genotypes presented. The TT genotype was most prevalent in household contacts (94.4%) followed by ENL (50%), and leprosy patients (44.4%). The CT genotype was most frequently detected in leprosy patients (50%), followed by ENL cases (44.4%), and household contacts (5.56%). In contrast, CC was mostly presented in ENL cases (5.56%), only 1% in leprosy patients, and absent among household contacts. Although the most prevalent allele in all three groups was the T allele, the C allele presented in 27% and 30% of ENL and leprosy patients, respectively and only 5% in household contact individuals. This study suggests that the polymorphism variations of IL-10 −819C/T are higher in leprosy and ENL patients compared to household contacts. Since this data is preliminary, larger studies are needed.